Countering abuse in EU environmental markets: The case for integrated operational safeguards - Kaime, Thoko (Review of European, Comparative & International Environmental Law, 2017)
Various European Union (EU) regulatory bodies have championed the use of environmental markets as a key policy tool to achieve environmental protection either in lieu of, or in addition to, more traditional regulatory programmes. When these markets work properly, they have the capacity to provide enhanced levels of environmental quality and can operate as more efficient mechanisms for protecting natural resources that provide vital services to people. However, if regulatory safeguards are absent from the legal frameworks creating such markets, it is unlikely that the theoretical benefits of these arrangements will be realized. This article assesses whether a number of EU environmental markets meet design standards that guard against these risks. It concludes that despite recognition of the danger of market manipulation and outright fraud, to date regulators in the EU have largely responded to these risks in an ad hoc and incomplete fashion, rather than embedding the mechanisms for operational accountability into the regulatory frameworks that govern green trading arrangements. Finally, this article identifies and prescribes five essential pillars for market-based programmes for the environment that are necessary to provide operational safeguards. These include informational safeguards, transparency standards, rule of law safeguards, verifiable performance standards and financial fidelity rules.
CRIS-Team Scopus Importer:2023-03-21